New Evidence on Mobility and Wages of the Young and the Old - Jörgen Hansen; Damba Lkhagvasuren (Institute for the Study of Labor (IZA), 2015)
We present new evidence on the wage and mobility of young and old workers, which is difficult to explain using standard human capital theory. Instead, we propose a simple dynamic extension of the Roy model, where worker migration and wages are jointly determined at the individual level. According to this model, a higher moving cost among older workers is the main factor driving the lower mobility among this group. Because of the higher moving costs, older workers require a higher wage increase to move across regions than younger workers, a pattern that is consistent with individual-level U.S. data. We also find an interesting dynamic effect suggesting that, given a persistent labor income shock, a higher future moving cost makes workers more mobile today.
Keywords: E24; J31; J61; R23; 330; geographic mobility; labor mobility by age; labor income shock; moving cost; multi-sector model